Noma (cancrum oris): An unresolved global challenge. Issue 1 (15th May 2019) - Feller, Liviu; Khammissa, Razia A. G.; Altini, Mario; Lemmer, Johan
Abstract: Noma (canrum oris) is a mutilating necrotizing disease of uncertain etiology, but it is accepted that it is caused primarily by a polybacterial infection with secondary ischemia. The consequent necrotizing fasciitis, myonecrosis, and osteonecrosis results in destruction of facial structures with severe functional impairment and disfigurement. It most frequently affects children, particularly in sub‐Saharan Africa, who are malnourished or debilitated by systemic conditions including but not limited to malaria, measles, and tuberculosis; and less frequently debilitated HIV‐seropositive subjects. In the vast majority of cases, in susceptible subjects, noma is preceded by necrotizing stomatitis. However, it has been reported, albeit rarely, that noma can arise without any preceding oral lesions being observed. Noma is not recurrent and is not transmissible.